2006
DOI: 10.1128/jcm.44.3.876-880.2006
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Detection and Identification of Candida , Aspergillus , and Cryptococcus Species by Reverse Line Blot Hybridization

Abstract: We report on a reverse line blot (RLB) assay, utilizing fungal species-specific oligonucleotide probes to hybridize with internal transcribed spacer 2 region sequences amplified using a nested panfungal PCR. Reference and clinical strains of 16 Candida species (116 strains), Cryptococcus neoformans (five strains of Cryptococcus neoformans var. neoformans, five strains of Cryptococcus neoformans var. grubii, and six strains of Cryptococcus gatti), and five Aspergillus species (68 strains) were all correctly ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 32 publications
1
35
0
Order By: Relevance
“…For nine specimens with a diagnosis of chronic 1 to 10 2 conidia/ml in normal saline. This is similar to the sensitivity of RLB observed in other studies (16,23). Further investigations using 10-fold serial dilutions of genomic DNA of A. fumigatus indicated that the minimum concentration that can be detected by the PCR/RLB assay is 1.8 ϫ 10…”
Section: Downloaded Fromsupporting
confidence: 66%
See 3 more Smart Citations
“…For nine specimens with a diagnosis of chronic 1 to 10 2 conidia/ml in normal saline. This is similar to the sensitivity of RLB observed in other studies (16,23). Further investigations using 10-fold serial dilutions of genomic DNA of A. fumigatus indicated that the minimum concentration that can be detected by the PCR/RLB assay is 1.8 ϫ 10…”
Section: Downloaded Fromsupporting
confidence: 66%
“…To allow optimal hybridization under the same conditions, probes were also designed to have similar physical characteristics: lengths between 20 and 28 bp and melting temperatures between 54.48°C and 63.68°C (Table 2). Oligonucleotide probes for Aspergillus species were used as described previously or modified from these previously described probes (16,23). Mucorales speciesspecific probes were designed by the authors, targeting ITS1 or ITS2 sequences ( Table 2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the use of oligonucleotide probes in reverse line blot (RLB) hybridization assays proved to be powerful for the identification of a diverse range of clinically relevant human and veterinary pathogens, with high throughput (14,40,42,44,54). Briefly, the RLB method enables the nonradioactive hybridization of PCR amplicons with different oligonucleotide probes in a single assay.…”
mentioning
confidence: 99%